An Experimental Study on the Laser Cladding Process for Refurbishing Shafts - YIN Song, LU Hai-feng, PAN Chen-yang, QIN En-wei, WU Shu-hui (Cailiao Baohu)
Shaft is one of the key components in mechanical facilities. Due to the effect of service environment, shaft always suffers from the normal damages such as surface wear damages, scratch and corrosion. In this work, preliminary experimental investigations were carried out on the possibility of using laser cladding for refurbishing shafts. For laying technical and theory foundations of post laser cladding, the trapezoidal and arc grooves on the bonding characterization between the cladding coating the substrate were studied against removing surface damages. The gradient distribution of chemical composition and hardness, the tensile behavior of the clad-substrate composite, and the wear behaviors at room temperature and high temperature of coatings after refurbishing treatment were analyzed. Results showed that laser cladding was proved to be as a promising technique in the application of shaft refurbishing.